2021
DOI: 10.21203/rs.3.rs-189281/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RNA-seq analysis reveals different transcriptomic responses to GA3 in early- and mid-season varieties before ripening initiation in sweet cherry (Prunus avium L.) fruits

Abstract: Gibberellin (GA) negatively affects color evolution and other ripening-related processes in non-climacteric fruits. The bioactive GA, gibberellic acid (GA3), is commonly applied at the light green-to-straw yellow transition to increase firmness and delay ripening in sweet cherry (Prunus avium L.), though causing different effects depending on the variety. Recently, we reported that GA3 delayed the IAD parameter (a ripening index) in a mid-season variety, whereas GA3 did not delay IAD but reduced it at ripeness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Cucurbitaceae is the second largest family bearing diverse groups of plant with broad range of fruit characteristic (Shaina and Suhara Beevy, 2012;Ma et al, 2020). Studies related to fruit development and variations in fruit sizes are also reported in other plants like Arabidopsis, tomato, pear, pumpkin, cucumber, bottle gourd, apple, Apricot, sweet cherry among many others (Jiang et al, 2015;Xanthopoulou et al, 2017;Di Marzo et al, 2020;Yuste-Lisbona et al, 2020;Zhang et al, 2020;Kuhn et al, 2021;Liu et al, 2023;Wang et al, 2022;Jahed and Hirst, 2023). RNA-Seq analyses have become the most popular method to identify the key genes regulating fruit morphology in several cucurbit vegetables (Zhang et al, 2016;Ma et al, 2020;Chen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Cucurbitaceae is the second largest family bearing diverse groups of plant with broad range of fruit characteristic (Shaina and Suhara Beevy, 2012;Ma et al, 2020). Studies related to fruit development and variations in fruit sizes are also reported in other plants like Arabidopsis, tomato, pear, pumpkin, cucumber, bottle gourd, apple, Apricot, sweet cherry among many others (Jiang et al, 2015;Xanthopoulou et al, 2017;Di Marzo et al, 2020;Yuste-Lisbona et al, 2020;Zhang et al, 2020;Kuhn et al, 2021;Liu et al, 2023;Wang et al, 2022;Jahed and Hirst, 2023). RNA-Seq analyses have become the most popular method to identify the key genes regulating fruit morphology in several cucurbit vegetables (Zhang et al, 2016;Ma et al, 2020;Chen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A coexpression analysis conducted at the onset of ripening (veraison) of two contrasting grapevine varieties during harvest revealed significant transcriptomic rearrangements that define the reprogramming of berry development (Fasoli et al, 2018). In the same line, a recent work of our group, conducted in two contrasting sweet cherry varieties with differences in the initiation of ripening, showed that they present significant differences at the transcriptomic level, including several genes involved in hormone biosynthesis and signaling, as well as transcriptional regulation (Kuhn et al, 2021b).…”
Section: Introductionmentioning
confidence: 86%
“…Our results suggest a possible role of ABA in ripening modulation by controlling the expression of the auxin response pathway. This pathway is also influenced by gibberellin in sweet cherry (Kuhn et al, 2021b), so a possibility arises where ABA and gibberellin control ripening initiation by regulating auxin response genes.…”
Section: Aba Modulates Pathways Related To Fruit Ripening At the Gene...mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that GA mainly exerted a negative role in the ripening and coloring process of sweet cherry. GA 3 application delays ABA accumulation, fruit size increase and ripening, reduces anthocyanin levels and produces fruits with less color (Kondo and Danjo, 2001;Usenik et al, 2005;Kuhn et al, 2021). GA 4 is also significantly and inversely correlated with the ripening parameters of sweet cherry (Teribia et al, 2016).…”
Section: Roles Of Plant Hormones In the Coloring Inhibition Induced B...mentioning
confidence: 99%